First-Line Durvalumab Plus Platinum-Etoposide Versus Platinum-Etoposide for Extensive-Stage Small-Cell Lung Cancer: A Cost-Effectiveness Analysis - Zhang, Longfeng; Hang, Yongfu; Liu, Maobai; Li, Na; Cai, Hongfu (Frontiers in Oncology, 2020)
BACKGROUND: The aim of the present study was to evaluate the cost-effectiveness of durvalumab plus platinum–etoposide versus platinum–etoposide as first-line treatments for small-cell lung cancer from the perspective of the US payer. METHODS: This study established a partition survival model for three health states, metastasis probability, and safety data based on the CASPIAN clinical trial. The health utility value was mainly derived from the published literature. Only direct medical costs were considered. Sensitivity analyses were conducted to assess the robustness of the incremental cost per quality-adjusted life year (QALY). RESULTS: Durvalumab plus platinum-etoposide increased QALY by 0.220 compared to that observed with platinum-etoposide only. The cost increased by $78,198.75, and the incremental cost per QALY increased by $355,448.86. One-way and probability sensitivity analyses indicated that the model parameters varied within a limited range and had no significant effect on the results. CONCLUSIONS: Although durvalumab plus platinum-etoposide can improve quality of life, it also substantially increases the cost of medical treatment. Under a willingness-to-pay threshold of $100,000, durvalumab does not have a cost-effective comparative advantage.